The Business Model Tested by the Digital Paradigm - Acquatella , François; Hlady-Rispal , Martine; Casteran , Gauthier; Jolivet , Vincent (American Journal of Management, 2021)
The accelerated digitization of an economy based on the exploitation of massive data and systems interoperability is reconfiguring the way in which new forms of digital organizations - "multisided platforms" - create value. However, little work has tested the business model (BM) concept with this new digital paradigm. In many respects, the new digital BMs (DBM) form a specific research object that requires an in-depth analysis of the new logics of creating, co-creating, shaping and capturing value within digital ecosystems. Our proposal in this paper is to analyze, at the theoretical level, the specificities associated with DBMs, in particular through an analytical reading of the main actors and value-generating mechanisms associated with them. We propose the conceptualization of a generic DBM and put forward a number of proposals for practitioners to "design" a DBM.